The Art of Film Acting : a Guide For Actors and Directors. - Comey, Jeremiah (Elsevier, 2002)
This guide for actors and directors develops a valid method for training performers to act from their core--whether they are cold reading, auditioning, or performing for film or television. This book teaches actors how to achieve and respond to believable and honest emotions before the camera, and it maintains that the key to a successful performance lies in how the actors relate to one another and to the circumstances. Exercises, including script examples, throughout the book give readers an easy resource for practicing the principles outlined. The Art of Film Acting applies a classic stage a.